The Treasury - Bridges, Lord. (London: George Allen & Unwin, 1964)
This book is one of a series about Government Departments sponsored by the Royal Institute of Public Administration.
Includes index.
Includes bibliographical references: p. 238-241.
ne 6/05/2018
Loan
Keywords: Government securities; United Kingdom